A Decision Support System For Construction Equipment Management Based On Data Warehousing Technique - Hassan, Bassam; Naja, Hani; Balouch, Ammar; makkiah, Samah (Latakia University Journal -Engineering Sciences Series, 2019)
As construction equipment is as considered the most important physical assets in construction companies. The effective equipment management, which is required to take the necessary operational and strategic decisions, is an urgent need to achieve the success of those companies. This include purchase, operation, retirement , renting, maintenance and repair..etc, with the least cost of operation as well as the best investment of the capital. The evolution in the use of automation technology and information management system associated with the increasing volume of collected equipment data, shows the need to a tool which enables to take an advantage of this huge collected data in equipment management. This research suggests a data warehouse for construction equipment management of engineering companies in the Syrian Public Sectors. This will improve the sources of data for the knowledge discovery. In addition, this research presents a primary decision support system which allows a visual analysis of the equipment data at different levels of details that helps equipment managers to fix the hidden problems behind operating equipment and then provide decision-making of equipment management at high level of flexibility.